Highly efficient mesenchymal stem cell proliferation on poly-ε-caprolactone nanofibers with embedded magnetic nanoparticles - Daňková, Jana; Buzgo, Matej; Vejpravová, Jana; Kubíčková, Simona; Sovková, Věra; Vysloužilová, Lucie; Mantlíková, Alice; Nečas, Alois; Amler, Evžen (International journal of nanomedicine, 2015)
In this study, we have developed a combined approach to accelerate the proliferation of mesenchymal stem cells (MSCs) in vitro, using a new nanofibrous scaffold made by needleless electrospinning from a mixture of poly-ε-caprolactone and magnetic particles. The biological characteristics of porcine MSCs were investigated while cultured in vitro on composite scaffold enriched with magnetic nanoparticles. Our data indicate that due to the synergic effect of the poly-ε-caprolactone nanofibers and magnetic particles, cellular adhesion and proliferation of MSCs is enhanced and osteogenic differentiation is supported. The cellular and physical attributes make this new scaffold very promising for the acceleration of efficient MSC proliferation and regeneration of hard tissues.
Keywords: magnetické nanočástice; tkáňové podpůrné struktury; Cell Adhesion; prasata; Cell Proliferation; Biocompatible Materials; Lactones; Tissue Engineering; tkáňové inženýrství; laktony; buněčná adheze; Mesenchymal Stem Cells; biokompatibilní materiály; Swine; buněčná diferenciace; proliferace buněk; nanovlákna; Magnetite Nanoparticles; zvířata; Caproates; mezenchymální kmenové buňky; Animals; Polyesters; Tissue Scaffolds; polyestery; kapronáty; Cell Differentiation; Nanofibers